2020
DOI: 10.1109/tuffc.2020.3005512
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Pleural Line Extraction and COVID-19 Scoring From Lung Ultrasound Data

Abstract: Recent works highlighted the significant potential of lung ultrasound (LUS) imaging in the management of subjects affected by COVID-19. In general, the development of objective, fast, and accurate automatic methods for LUS data evaluation is still at an early stage. This is particularly true for COVID-19 diagnostic. In this article, we propose an automatic and unsupervised method for the detection and localization of the pleural line in LUS data based on the hidden Markov model and Viterbi Algorithm. The pleur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
100
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(103 citation statements)
references
References 32 publications
(36 reference statements)
0
100
0
Order By: Relevance
“… FC-Densenet103, Unet, DenseNet, and DenseNet121-FPN. References References [ 137 ] [ 138 ] [ 139 ] [ 140 ] [ 141 ] [ 142 ] [ 143 ] [ 129 ] [ 144 ] [ 145 ] [ 146 ] [ 147 ] [ 148 ] [ 149 ] [ 150 ] [ 151 ] [ 152 ] [ 153 ] [ 154 ] [ 155 ] [ 156 ] [ 157 ] [ 158 ] [ 159 ] [ 160 ] [ 161 ] [ 162 ] [ 163 ] [ 164 ] [ 165 ] Classification Characteristics Characteristics Gray scale feature extraction and ML classifier, and model-based techniques. Resnet-50, CNN, SVM, ResNet101, VGG16, and VGG19.…”
Section: Artificial Intelligence Architectures For Ards Characterizatmentioning
confidence: 99%
See 2 more Smart Citations
“… FC-Densenet103, Unet, DenseNet, and DenseNet121-FPN. References References [ 137 ] [ 138 ] [ 139 ] [ 140 ] [ 141 ] [ 142 ] [ 143 ] [ 129 ] [ 144 ] [ 145 ] [ 146 ] [ 147 ] [ 148 ] [ 149 ] [ 150 ] [ 151 ] [ 152 ] [ 153 ] [ 154 ] [ 155 ] [ 156 ] [ 157 ] [ 158 ] [ 159 ] [ 160 ] [ 161 ] [ 162 ] [ 163 ] [ 164 ] [ 165 ] Classification Characteristics Characteristics Gray scale feature extraction and ML classifier, and model-based techniques. Resnet-50, CNN, SVM, ResNet101, VGG16, and VGG19.…”
Section: Artificial Intelligence Architectures For Ards Characterizatmentioning
confidence: 99%
“… Resnet-50, CNN, SVM, ResNet101, VGG16, and VGG19. References References [ 166 ] [ 167 ] [ 168 ] [ 169 ] [ 170 ] [ 148 ] [ 150 ] [ 151 ] [ 171 ] [ 152 ] [ 153 ] [ 157 ] [ 158 ] [ 159 ] [ 172 ] [ 173 ] [ 174 ] [ 175 ] Joint Segmentation and Classification Characteristics Characteristics They use the same characteristics as adapted by segmentation and classification domain for AI-based Non-ARDS. They use the same characteristics as adapted by segmentation and classification domain for AI-based ARDS.…”
Section: Artificial Intelligence Architectures For Ards Characterizatmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the ultrasound dataset related to COVID-19 is severely limited and a considerable amount of annotated dataset is still publicly unavailable, very few research results have been reported so far on LUS considering the contemporary studies. Among them, in [ 7 , 17 ], LUS has been employed to detect specific patterns of the disease as well as the disease severity in terms of various scores. In this regard, both deep learning and machine learning techniques are implemented for automatic disease prediction in the current resource-con-strained environment.…”
Section: Introductionmentioning
confidence: 99%
“…On top of that, they published a subset of the dataset they utilized in the study, comprising a total of 60 videos, among which 58 videos are fully labeled at the frame level. In [ 17 ], an SVM-based classification model is proposed following the automatic localization of the pleural line by the hidden Markov Model and the Viterbi algorithm. Here, the authors utilized the dataset released by [ 7 ] and to deal with the limitation of available data, they limited the study on hospital-specific cases and deployed a machine learning model.…”
Section: Introductionmentioning
confidence: 99%